Knowledge and power: The illusion of emancipatory pedagogies within environmental education - Roger Firth (Environmental Association of Southern Africa, 1996)
The increased calls for transformation in response to the socio-ecological 'crisis' and the movement towards more sustainable societies; the dramatic political changes in South Africa, Eastern Europe and elsewhere; the epistemological shifts in the conceptualisation of science, education and research, and the paradoxes of the world of the late twentieth century provide the context for this paper. The need for educational organisations and educators to make an effective curriculum response to environmental and development concerns legitimises socially critical approaches to environmental education and a concern with processes of social change. We are faced, therefore, with dilemmas of personal, professional and political change: the need for transformation of both actors and structures. The paper highlights the unquestioned assumptions which underlie growing calls for social transformation and considers the significance of a socially critical orientation to environmental education in relation to processes of social change. This orientation draws on the critical theories underpinning 'liberatory' or 'emancipatory' pedagogies,akeyconcern being the need to 'empower' perceived 'marginalised' groups and individuals and for 'transformatory intellectuals' to support 'capacity building' among such marginalised groups and individuals. I highlight a number of concerns I have about this orientation and emphasise the need to re-think some aspects of the project. The theoretical considerations of the paper are borne out of particular instances of trying to actualise the aims of a socially critical environmental education, both within my professional practice as a teacher educator, and as a result of a school based collaborative action research project with a small group of primary teachers (this is reported elsewhere).